Morphophysiological evaluation of hybrid maize lines from peak and test crosses for high-yield development - NASARUDDIN NASARUDDIN; MUH. FARID; MUHAMMAD FUAD ANSHORI; AMIN NUR; NENI IRIANY; ANNASTYA NUR FADHILAH (Society for Indonesian Biodiversity, 2025)
Abstract. Nasaruddin, Farid M, Anshori MF, Nur A, Iriany N, Fadhilah AN. 2025. Morphophysiological evaluation of hybrid maize lines from peak and test crosses for high-yield development. Biodiversitas 26: 5204-5210. The increasing demand for maize in Indonesia amid stagnant productivity underscores the need for innovative breeding approaches to enhance yield potential and resilience. This study integrates morphophysiological trait analysis with hybrid maize lines derived from transgressive segregants and elite line, aiming to identify promising genotypes and key traits associated with high productivity under tropical conditions. A total of 96 genotypes, consisting of 60 hybrids, 20 parental lines and 4 commercial controls, were evaluated using an augmented design. Observations were made on agronomic and physiological traits. This is the first report combining peak and test cross schemes with morphophysiological evaluation in tropical maize, which broadens the genetic base and addresses the limitation of narrow parental pools. Several hybrid maize lines, particularly G29 (8.7 t.ha-1), G28, and G39, outperformed their parents in yield performance. Traits such as cob weight, number of seeds per row, and plant height exhibited high heritability and strong direct effects on yield, highlighting their suitability as selection criteria in breeding programs. Overall, integrating source traits (e.g., plant height, chlorophyll index) and sink traits (e.g., cob characteristics) provides an effective strategy for developing high-yielding and resilient maize hybrids suitable for smallholder-based production systems in tropical environments.